Early Carboniferous ammonoid faunas and stratigraphy of the Montagne Noire (France) - D. Korn; R. Feist (Fossil Record, 2007)
The early Carboniferous (Mississippian) sedimentary succession of the Montagne Noire is subdivided into three major lithostratigraphic units, in ascending order the Montagne Noire Griotte Group (Devonian to Early Tournaisian), the Tournaisian to Viséan Saint-Nazaire Group (with the Lydiennes, Faugères, Colonnes, and Puech Capel Formations, the latter new), and the Laurens Flysch Group (late Viséan). The ammonoid assemblages in these rock units are reviewed. A total of 29 Early Carboniferous ammonoid taxa at species level are determined. The new genus Nigrocyclus n. gen., and the new species Gattendorfia nazairensis n. sp., Globimitoceras albaillei n. sp., and Neogoniatites canovasi n. sp. are described. Die unterkarbonische Abfolge von Sedimentgesteinen in der Montagne Noire wird in drei lithostratigraphische Einheiten untergliedert, von unten nach oben die Montagne Noire Griotte Gruppe (Oberdevon bis Untertournai), die Saint-Nazaire Gruppe des Tournaisium und Viséum (mit den Lydiennes Faugères, Colonnes und Puech Capel Formationen, von denen die letzte neu ist), und der Laurens Flysch Gruppe (Oberviséum). Die Ammonoideen-Vergesellschaftungen in diesen Gesteinen werden revidiert. Insgesamt werden 29 unterkarbonische Ammonoideen-Taxa auf Artebene aufgeführt; neu beschrieben werden die Gattung Nigrocyclus n. gen. sowie die Arten Gattendorfia nazairensis n. sp., Globimitoceras albaillei n. sp. und Neogoniatites canovasi n. sp. doi:10.1002/mmng.200700002